Editorial Board (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Editorial Board:Carl BurkartAlexa Collesides (Editorial Team Member)Ruud DuvekotSusan ForseilleAmy Giaculli (Associate Editor)Alan MandellNan Travers